2023
DOI: 10.1002/aic.18014
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of phenylacetic acid in block copolymer nanoparticles during polymerization induced self‐assembly

Abstract: Polymerization induced self-assembly (PISA) is an in situ method for producing block copolymer nanoparticles. Performing PISA in the presence of a pharmaceutical drug causes the nanoparticles to encapsulate the drug. While this approach is straightforward, the effects of drug loading and block copolymer composition remain unclear. Here, we investigate encapsulation of the drug phenylacetic acid (PA) in poly(glycerol monomethacrylate)-block-poly(2-hydroxypropyl methacrylate) (PGMA-PHPMA) nanoparticles during PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…106 Conducting PISA in the presence of curcumin (Figure 5, Structure II) as a model drug revealed that its presence alters the morphological evolution during the PISA process (Figure 6). Li et al 107 found similarly facilitated morphological transitions upon increasing the targeted loading with the drug PA.…”
Section: Physical In Situ Encapsulationmentioning
confidence: 89%
See 3 more Smart Citations
“…106 Conducting PISA in the presence of curcumin (Figure 5, Structure II) as a model drug revealed that its presence alters the morphological evolution during the PISA process (Figure 6). Li et al 107 found similarly facilitated morphological transitions upon increasing the targeted loading with the drug PA.…”
Section: Physical In Situ Encapsulationmentioning
confidence: 89%
“…Considering the challenge of solubilizing hydrophobic cargo in the reaction mixture, PISA systems that aim for physical in situ cargo encapsulation generally yield low cargo loadings. In the exceptional cases where high cargo loadings are achieved 106 and/or amphiphilic drugs such as phenylacetic acid (PA; Figure 5, Structure IV ) 107 are used, the cargo location within the nanoparticle should be considered as it may influence the NP behavior in a biological environment. The location of the cargo may not be limited to the hydrophobic core, but sequestration into the hydrophilic shell can occur 129 .…”
Section: (Therapeutic) Cargo Encapsulation In Pisa‐npsmentioning
confidence: 99%
See 2 more Smart Citations